2016
DOI: 10.1521/aeap.2016.28.6.511
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated With Repeated HIV Testing Among Internet-Using Men Who Have Sex With Men

Abstract: Background Men who have sex (MSM) with men represent a disproportionately impacted risk group for HIV incidence among at-risk U.S. populations. Few studies have identified risk factors associated with HIV testing frequency both within and outside of traditional healthcare setting. Methods MSM enrolled in a prospective cohort, were mailed at-home specimen collection kit and followed for a year. Incidence density rate ratios (IDRR) of testing were calculated and generalized estimating equations were used to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
2
3
0
Order By: Relevance
“…Among behavioral predictors, the odds of having tested within at least the last 12 months were higher among those who reported having engaged in CAS with a casual partner in the last year when compared to those who had not. This finding is consistent with several past studies (Johnson et al, 2016; Rendina et al, 2014; Rowe et al, 2017), and suggests that those who are at highest risk for HIV are more likely to have tested recently. Our results also suggested that MSM who reported recent injection drug use were less likely to have tested within the CDC-recommended intervals.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Among behavioral predictors, the odds of having tested within at least the last 12 months were higher among those who reported having engaged in CAS with a casual partner in the last year when compared to those who had not. This finding is consistent with several past studies (Johnson et al, 2016; Rendina et al, 2014; Rowe et al, 2017), and suggests that those who are at highest risk for HIV are more likely to have tested recently. Our results also suggested that MSM who reported recent injection drug use were less likely to have tested within the CDC-recommended intervals.…”
Section: Discussionsupporting
confidence: 92%
“…Testing rates were especially high among African American, Hispanic/Latino, and multiracial MSM, with over two-thirds of these participants having tested at least once in the last 6 months. These findings are consistent with some past studies (e.g., Johnson et al, 2016; Rendina et al, 2014), but contrast with others showing no differences in testing rates in racial/ethnic minority MSM compared to White MSM (Khosropour et al, 2013; Margolis et al, 2012). Together, these findings suggest that continued efforts to connect those with less formal education with testing are needed, but that similar efforts to boost testing among African American and Hispanic/Latino MSM in the Northeast may be making progress toward addressing high HIV incidence in these subgroups.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is likely due to the result of increased HIV testing among minority groups, who are less likely to report never testing for HIV. (32) It should be noted, however, that lower odds of unknown HIV status does not suggest minority MSM are less likely have an undiagnosed HIV infection. It is more likely a reflection of testing services often targeted toward minority populations, and perhaps it is the proportion of those populations who are not being tested that remain unaware of their infection.…”
Section: Discussionmentioning
confidence: 98%
“…Both regular and risk-based testers could also have a chance to become opportunistic testers and test outside of their regular testing interval or in the absence of a specific sexual episode, respectively, when opportunities were available. In addition, many public health agencies recommend different testing frequencies for MSM at higher vs. lower risk for HIV acquisition [32][33][34][35] and evidence suggests that MSM at higher risk test more frequently on average [36][37][38][39][40][41]. As a result, we stratified regular testers into high vs. low anal intercourse (AI) frequency groups in order to allow for differential testing frequencies by risk.…”
Section: Hiv Transmission and Progressionmentioning
confidence: 99%